Evaluating the safety impacts of powered two wheelers on a shared roadway in China using automated video analysis. Issue 4 (4th July 2019) - Guo, Yanyong; Sayed, Tarek; Zaki, Mohamed H.
ABSTRACT: The last decade witnessed a rapid growth in the number of powered two wheelers (PTWs) on Chinese roads. PTWs offer a convenient, flexible, and affordable mobility solution. They are also considered as an environment-friendly alternative to automobiles. Despite these advantages, concerns have been raised about the safety impacts of PTWs on China's urban roadways. The main objective of this study is to evaluate the safety impacts of PTWs on a shared roadway in Kunming, China, using automated computer video analysis. The study pursues the following tasks: (1) to perform a comprehensive safety analysis based on the automated traffic conflict techniques, (2) to analyze the nonconforming (NC) travel behaviors of PTWs, (3) to examine the relationship between the detected traffic conflicts and the PTWs travel behaviors, and (4) to study the steering action of PTWs by estimating their movement yaw rate. The automated analysis revealed several findings regarding the PTWs travel behaviors on the shared roadway. The results showed that a considerable number of conflicts with high severity were caused by PTWs on the shared roadway. It was observed that PTWs are likely to engage in NC behaviors while traveling on the shared roadway. Also, more than one half of the NC behavior events resulted in PTW conflicts. On the other hand, the yaw rate analysis showed that not every PTW took swerving maneuvers when involved in a conflict situation. The findings in the article identify the hazardous travel behavior associated with PTWs. Such behavior can have negative safety consequences on roadways shared with more vulnerable road users such as cyclists.